2021
DOI: 10.1590/1678-5150-pvb-6717
|View full text |Cite
|
Sign up to set email alerts
|

Molecular detection of Apicomplexa protozoa in tissues from Alouatta guariba clamitans

Abstract: The brown howler monkey (Alouatta guariba clamitans) is a primate species widely distributed in South America. Infections by protozoa are common in primates. However, studies on protozoa in primates in Brazil are scarce, so the goal of this study was to investigate DNA from the apicomplexan protozoa Neospora caninum, Sarcocystis spp. and Toxoplasma gondii in tissues of A. guariba clamitans. DNA extraction was performed on tissue samples from the heart, brain, liver, spleen, lung and intestine of six A. guariba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…Another study has shown 4.7% (91/1921) of bats with tissues positive for the 18S rDNA gene were detected, and eight genera of protozoa of the Sarcocystidae family (Besnoitia, Cystoisospora, Hammondia, Hyaloklossia, Neospora, Nephroisospora, Sarcocystis, and Toxoplasma) were identified in 50 samples of 16 bat species (belonging to the families Phyllostomidae, Molossidae, and Vespertilionidae) in the state of São Paulo (Cabral et al, 2021). In addition, Ludwig et al (2021) detected the 18S rDNA gene in brain and heart tissue from six brown howler monkey (Alouatta guariba clamitans) and identified the genus Sarcocystis (4/6) and Toxoplasma (2/6). 2018) isolated and genotypically characterized T. gondii from wild free-ranging or captive birds in the state of Pernambuco, Brazil, and described a non-virulent isolate of T. gondii in a free-living green-backed heron (Butorides striata).…”
Section: Discussionmentioning
confidence: 99%
“…Another study has shown 4.7% (91/1921) of bats with tissues positive for the 18S rDNA gene were detected, and eight genera of protozoa of the Sarcocystidae family (Besnoitia, Cystoisospora, Hammondia, Hyaloklossia, Neospora, Nephroisospora, Sarcocystis, and Toxoplasma) were identified in 50 samples of 16 bat species (belonging to the families Phyllostomidae, Molossidae, and Vespertilionidae) in the state of São Paulo (Cabral et al, 2021). In addition, Ludwig et al (2021) detected the 18S rDNA gene in brain and heart tissue from six brown howler monkey (Alouatta guariba clamitans) and identified the genus Sarcocystis (4/6) and Toxoplasma (2/6). 2018) isolated and genotypically characterized T. gondii from wild free-ranging or captive birds in the state of Pernambuco, Brazil, and described a non-virulent isolate of T. gondii in a free-living green-backed heron (Butorides striata).…”
Section: Discussionmentioning
confidence: 99%
“…Monkeys of the genus Aotus are socially monogamous and are the only genus of Neotropical primates that are nocturnal, or cathemeral [58]. Owl monkeys' distribution ranges from Bolivia and Paraguay to Northern Argentina [59].…”
Section: Aotus Azarae (Owl Monkey)mentioning
confidence: 99%
“…Mammals are a potential reservoir for many zoonotic pathogens, including Apicomplexa taxa such as Sarcocystis spp., Cryptosporidium spp., or Toxoplasma gondii [1,2]. This phylum, also called Sporozoa, is a diverse group of protozoan parasites, that are unicellular eukaryotes and obligate intracellular without flagella, and were detected in different mammalian organs [3][4][5]. Using their apical complex and their secretory organelle structure, they invade the host cell [6], potentially causing chronic asymptomatic diseases or severe acute diseases in endemic areas (Beck et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…in the tongue muscles of armadillos [9], in wild birds [10] or Toxoplasma gondii and Sarcocystis spp. detected in the Alouatta guariba clamitans [5]. Except for T. gondii [3,11], there are no data on the description of such parasites circulating in French Guiana, strongly hampering the assessment of the risk of human transmission.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation